The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1136/heartjnl-2020-317802
|View full text |Cite
|
Sign up to set email alerts
|

The effect of green Mediterranean diet on cardiometabolic risk; a randomised controlled trial

Abstract: BackgroundA Mediterranean diet is favourable for cardiometabolic risk.ObjectiveTo examine the residual effect of a green Mediterranean diet, further enriched with green plant-based foods and lower meat intake, on cardiometabolic risk.MethodsFor the DIRECT-PLUS parallel, randomised clinical trial we assigned individuals with abdominal obesity/dyslipidaemia 1:1:1 into three diet groups: healthy dietary guidance (HDG), Mediterranean and green Mediterranean diet, all combined with physical activity. The Mediterran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 29 publications
5
41
0
Order By: Relevance
“…However, all 5 reviewed studies included either added exercise or calorie restriction, confounding the effects of the dietary change. A later randomized trial reported significant weight loss with a Mediterranean diet, but the study also included a substantial energy restriction and physical exercise (6). In the Lyon Diet Heart Study (7), a Mediterranean diet supplemented with an alpha-linolenic-acid-rich margarine reduced cardiac deaths and nonfatal myocardial infarctions in individuals who had survived a myocardial infarction but led to a small weight gain (1.4 kg) during the 2-year study, rather than weight loss (8).…”
Section: Introductionmentioning
confidence: 99%
“…However, all 5 reviewed studies included either added exercise or calorie restriction, confounding the effects of the dietary change. A later randomized trial reported significant weight loss with a Mediterranean diet, but the study also included a substantial energy restriction and physical exercise (6). In the Lyon Diet Heart Study (7), a Mediterranean diet supplemented with an alpha-linolenic-acid-rich margarine reduced cardiac deaths and nonfatal myocardial infarctions in individuals who had survived a myocardial infarction but led to a small weight gain (1.4 kg) during the 2-year study, rather than weight loss (8).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we demonstrated the polyphenols found in Mankai. Our previous work described the beneficial effect of Mankai on glycemic response [52], cardiovascular risk [29], the gut microbiome [53] and liver steatosis [30]. Our previous and current observations regarding the Mankai plant may contribute to better understanding the effect of this plant on health.…”
Section: Discussionmentioning
confidence: 77%
“…The mean body mass index (BMI) of the participants was 31.3 ± 4.0 kg/m 2 , and the mean WC was 110.6 ± 9.1 cm for men and 103.3 ± 9.6 cm for women. All baseline characteristics (e.g., weight: 93.7 ± 14.3, WC: 109.7 ± 9.5, systolic blood pressure: 130.3 ± 14.0, diastolic blood pressure: 81.1 ± 10.2; data presented for the entire study population) did not differ between the intervention groups [29,30]. Ten polyphenols were detected in the participants' baseline plasma samples, with no significant differences between groups (Table 2).…”
Section: Direct Plus Baseline Characteristicsmentioning
confidence: 97%
See 2 more Smart Citations